2011
DOI: 10.1254/jphs.11013fp
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Citidine-5-diphosphocholine on Impaired Spatial Memory in a Rat Model of Cerebrovascular Dementia

Abstract: Abstract. Citidine-5-diphosphocholine or citicoline (CDP-choline) is used as a neuroprotective and memory-enhancing drug in cerebral stroke, Alzheimer's disease, and other neurovascular diseases. Non-clinical studies have demonstrated the neuroprotective effects of CDP-choline in ischemic animal models. However, the relationship between the neuroprotective effect and the memory enhancing effect of CDP-choline is still unknown. No studies have demonstrated the ameliorative effect on impaired spatial memory and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 28 publications
0
16
0
3
Order By: Relevance
“…Citicoline has been found to improve spatial memory after brain ischemia 48 and CCI 20 in rats, but the present one is, to our knowledge, the first report of citicoline benefits on ORM after an experimental model of TBI. In contrast, mixed results have been obtained in human TBI patients.…”
Section: Citicoline Improved Memory In Tbi Animals But the Mechanismmentioning
confidence: 50%
“…Citicoline has been found to improve spatial memory after brain ischemia 48 and CCI 20 in rats, but the present one is, to our knowledge, the first report of citicoline benefits on ORM after an experimental model of TBI. In contrast, mixed results have been obtained in human TBI patients.…”
Section: Citicoline Improved Memory In Tbi Animals But the Mechanismmentioning
confidence: 50%
“…In a clinical study, donepezil shortened NREM sleep and increased the amount of REM sleep [22] Ishida and Kamei also reported that donepezil resulted in an increased wakefulness time and decreased NREM sleep time in naïve rats during 3 h after treatment at a dose of 3 mg/kg [23]. Because our previous studies demonstrated that donepezil treatment reduced cognitive dysfunction in cerebral ischemia-treated rats at doses of 3 and 10 mg/kg [24], we evaluated the sleep-wakefulness profile at the lower donepezil dose in the present study. Therefore, other different times and doses of donepezil treatment may affect the sleep-wakefulness profile in cerebral ischemiatreated rats.…”
Section: Yokukansan Reduces Sleep Disturbancementioning
confidence: 99%
“…Interestingly, in vitro , CDP-choline or citicoline, a precursor for phosphatidylcholine and subsequently, sphingomyelin biosynthesis from ceramide prevented ethanol-induced apoptosis in these cells. CDP-choline has also been shown to alleviate neurodegeneration and stroke damage in human trials [164, 251, 252]. Choline is a rich source for methyl groups required to synthesize phosphatidylcholine in the Kennedy pathway of glycerophospholipid biosynthesis (Fig.…”
Section: Conclusion and Hypothesis: Developmental Niches May Be Mmentioning
confidence: 99%